2016
DOI: 10.18632/oncotarget.8446
|View full text |Cite
|
Sign up to set email alerts
|

The biology of DHX9 and its potential as a therapeutic target

Abstract: DHX9 is member of the DExD/H-box family of helicases with a “DEIH” sequence at its eponymous DExH-box motif. Initially purified from human and bovine cells and identified as a homologue of the Drosophila Maleless (MLE) protein, it is an NTP-dependent helicase consisting of a conserved helicase core domain, two double-stranded RNA-binding domains at the N-terminus, and a nuclear transport domain and a single-stranded DNA-binding RGG-box at the C-terminus. With an ability to unwind DNA and RNA duplexes, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
143
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(145 citation statements)
references
References 216 publications
(280 reference statements)
2
143
0
Order By: Relevance
“…A comparison of these data sets shows significant overlap in the identity of gene products affected by the depletion of either protein (287 genes with altered expression upon DHX9 or Nup98 depletion, p=3.24×10 −36 ; see Material and methods), consistent with the idea that these proteins form a functional complex. Interestingly, a significant number (p-value 2.38 × 10 −4 ) of those genes exhibiting altered expression upon Nup98 depletion contain a putative cAMP-response element (CRE) (Zhang et al, 2005), a regulatory element whose transcriptional activity can be regulated by DHX9 (Aratani et al, 2001; Fidaleo et al, 2016; Lee and Pelletier, 2016).
10.7554/eLife.18825.024Figure 11.Nup98 or DHX9 depletion alters the abundance of target mRNAs.HEK293T cells were transduced with a control shRNA or an shRNA targeting Nup98 or DHX9.
…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of these data sets shows significant overlap in the identity of gene products affected by the depletion of either protein (287 genes with altered expression upon DHX9 or Nup98 depletion, p=3.24×10 −36 ; see Material and methods), consistent with the idea that these proteins form a functional complex. Interestingly, a significant number (p-value 2.38 × 10 −4 ) of those genes exhibiting altered expression upon Nup98 depletion contain a putative cAMP-response element (CRE) (Zhang et al, 2005), a regulatory element whose transcriptional activity can be regulated by DHX9 (Aratani et al, 2001; Fidaleo et al, 2016; Lee and Pelletier, 2016).
10.7554/eLife.18825.024Figure 11.Nup98 or DHX9 depletion alters the abundance of target mRNAs.HEK293T cells were transduced with a control shRNA or an shRNA targeting Nup98 or DHX9.
…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, it is intriguing that DHX9, an NTP-dependent DNA and RNA helicase, was identified. DHX9 reportedly interacts with G quadruplexes and antiparallel DNA triple helices (24). Thus, DHX9 may contribute to the unwinding of the MALAT1 triple helix, possibly the first step in the 3′-5′ decay of MALAT1.…”
Section: Discussionmentioning
confidence: 99%
“…One of these helicases is DHX9 (also known as RHA), a highly abundant and multifunctional RNA/DNA helicase involved in DNA replication, transcription, and posttranscriptional and translational regulation (201). It contains two tandem repeats of dsRBDs followed by the DExH-motif helicase domain, and it displays an ATP-driven dsRNA-unwinding activity (201). Earlier studies showed that DHX9 is packaged into HIV-1 virions and is a host factor necessary for HIV-1 replication (202).…”
Section: Helicases (Besides Rlrs and Dicer)mentioning
confidence: 99%